2021
DOI: 10.1155/2021/6868625
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Warm Needle Acupuncture on Temporomandibular Joint Disorders: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background. Temporomandibular joint disorders (TMDs) are a common and prevalent disease with main symptoms of pain, joint sounds, and mandibular movement disorders, which seriously affects the mental health and quality of life of the sufferers. In recent years, there have been an increasing number of studies utilizing warm needle acupuncture (WNA) for the treatment of TMD, and the quality of the studies has gradually improved. However, evidence from evidence-based medicine is lacking. This study aims to use a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Complementary and alternative medicine (CAM) practitioners that help conventional a holistic dentists include chiropractors, pharmacist, acupuncturists, acupressurists, therapists and nutritionists (Liu, et al, 2021).…”
Section: Integrative and Complementary Practices In Dentistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Complementary and alternative medicine (CAM) practitioners that help conventional a holistic dentists include chiropractors, pharmacist, acupuncturists, acupressurists, therapists and nutritionists (Liu, et al, 2021).…”
Section: Integrative and Complementary Practices In Dentistrymentioning
confidence: 99%
“…Acupuncture on temporomandibular Joint Disorders: A Systematic Review and Meta-Analysis of Randomized Controlled Trials (Liu, et al, 2021) Use the method of systematic review and meta-analysis to understand the effectiveness of WNA (Warm Needle Acupuncture) for treating TMD.…”
Section: Effects Of Warm Needlementioning
confidence: 99%
“…The Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) were established to precisely differentiate the symptoms, which are difficult to quantify, in order to enable uniform diagnosis against a background of high prevalence [ 10 ]. Despite generally valid and uniform diagnostic criteria, the therapeutic strategies published in the literature are diverse and range from analgesic or anti-inflammatory drugs, occlusal splints, physical therapies, trigger point injections, and acupuncture to Botox injections and lasers [ 11 , 12 , 13 , 14 , 15 , 16 ]. In this regard, a recent systematic review and meta-analysis explicitly reported the efficacy of all therapeutic approaches for TMD with exclusively a muscular origin [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, clinicians can use a variety of acupuncture modalities, such as electroacupuncture, warm acupuncture, and hand acupuncture. [4,5] Funded by Hangzhou science and technology bureau project (2021K1662).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, clinicians can use a variety of acupuncture modalities, such as electroacupuncture, warm acupuncture, and hand acupuncture. [ 4 , 5 ] Stimulation of acupuncture points by acupuncture has been shown to induce analgesia by releasing neuropeptides such as enkephalins, dynorphins, beta-endorphins, and endorphins. [ 6 ] A recent systematic review suggests that acupuncture can reduce PHPS pain in the short term, however, more nuanced issues, such as how practitioners choose different acupuncture in different situations, remain unclear.…”
Section: Introductionmentioning
confidence: 99%